2003
DOI: 10.1017/s0020818303573076
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Influence: Interest Groups and Congressional Voting on Trade Policy

Abstract: Studies of the effects of interest groups on congressional roll-call voting typically view party and ideology as competing factors and rely on a factoral model of interests or a sectoral model including only interest groups with a direct stake in the vote. We depart from that strategy in several ways. We define interest groups at the level of Standard Industrial Classification two-digit codes and observe the universe of interests. For 1979–90, we use measures of geographically and nongeographically based econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 52 publications
0
67
0
5
Order By: Relevance
“…Thus, DW-NOMINATE incorporates both constituency and personal ideological beliefs. See Fleck and Kilby (2002) and Fordham and McKeown (2003). This preliminary investigation has revealed that average support for the IMF is higher in the Senate than in the House, and that House support has declined in correlation with the trade balance.…”
Section: Congress and Imf Funding Increasesmentioning
confidence: 94%
“…Thus, DW-NOMINATE incorporates both constituency and personal ideological beliefs. See Fleck and Kilby (2002) and Fordham and McKeown (2003). This preliminary investigation has revealed that average support for the IMF is higher in the Senate than in the House, and that House support has declined in correlation with the trade balance.…”
Section: Congress and Imf Funding Increasesmentioning
confidence: 94%
“…They can also engage in outside lobbying (Kollman, 1998), aimed at influencing public opinion by way of campaigns and similar activities. Furthermore, they can influence the selection of decision-makers (Fordham and McKeown, 2003), for example by getting involved in election campaigns or by trying to have some bearing on the appointment of Rapporteurs in the European Parliament. Finally, interest groups may wield structural power, that is, influence decisionmakers simply because of the impact that business decisions about whether to invest in a specific area can have on public policy (Lindblom, 1977;Bernhagen and Bräuninger, 2005).…”
Section: The Challengementioning
confidence: 99%
“…a whole+ Historically, however, open trade has been the exception rather than the rule+ Studies of the political economy of trade often attribute variations in trade preferences to the distributional implications of overseas commerce+ Despite the economic benefits that a given country would accrue from open trade, some individuals suffer economic harm as a result+ If these individuals form a politically potent constituency, they may be able to pressure policymakers to increase trade barriers even if doing so is economically counterproductive for the country as a whole+ If, on the other hand, the individuals who derive welfare gains from trade are particularly influential, then an open trade regime is likely to take hold+ Recent research indicates that, in democratic countries, constituency opinion on trade plays a central role in influencing the policy positions of public officials+ 2 There are two principle ways of assessing the distributional consequences of trade+ First, the factor endowments approach emphasizes that, in a given country, trade benefits those individuals who own factors of production that are in abundant supply relative to the remainder of the world, and harms owners of factors that are in scarce supply+ In countries such as the United States, which has a skilled labor force, free trade benefits highly skilled workers and harms less skilled workers+ Second, the specific factors approach predicts that an individual's attitudes toward trade will reflect characteristics of the industry in which he or she works+ People employed in industries that depend on overseas markets should be more supportive of open trade than people working in industries that face considerable competition from imports+ A small but growing number of studies have evaluated the strength of these explanations for trade policy preferences+ We extend this body of research using two representative national surveys of Americans and more comprehensive measures of industries and occupations than previous studies had available to them+ In addition, we link the study of trade preferences to the more extensive body of theory and empirical research on how self-interest enters into the formation of domestic economic policy preferences+ Substantial research in other economic policy domains has demonstrated that self-interest rarely shapes the formation of policy opinions because people have a difficult time understanding the connection between personal economic wellbeing and government policy+ By mounting the most thorough individual-level examination to date of the effects of industry and skill on individual trade preferences, we seek to determine whether trade is, indeed, one of those rare exceptions in which personal experiences are successfully politicized+ Alternatively, if attitudes about trade are formed in a manner similar to attitudes about domestic economic domains such as unemployment, then trade policy preferences will be based on how people believe a policy affects the country collectively rather than on narrowly defined self-interest+ Importantly, the analysis of aggregate-level data-the 2+ See Fordham and McKeown 2003;and Kono 2008+ approach used by most previous studies of trade preferences-cannot differentiate between these two possibilities+ Thus, uniquely, this study simultaneously examines both how personal economic self-interest and perceptions of the collective national interest influence trade preferences+ Our findings indicate that accounting for perceptions of how the U+S+ economy is affected by trade is important to modeling trade preferences+ Consistent with previous research on the impact of self-interest on policy attitudes, our data show little support for either the factor endowments or the specific factors model+ By contrast, perceptions of how trade affects the country as a whole-what are often referred to as "sociotropic" perceptions-play a substantial role in shapi...…”
mentioning
confidence: 99%